On rational functions with monodromy group M11. (March 2017) - König, Joachim
Abstract: We compute new polynomials with Galois group M 11 over Q ( t ) . These polynomials stem from various families of covers of P 1 C ramified over at least 4 points. Each of these families has features that make a detailed study interesting. Some of the polynomials lead, via specialization, to number fields with very small discriminant or few ramified primes.